(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The dynamically changing environment makes companies become intelligent organizations. This means that the basis for their functioning is not only the knowledge that they acquire, but also that the companies skilfully use and create new knowledge. This allows firms to introduce new ideas, which help them thrive on the market.